Case report: Complete remission of bone metastasis from renal cell carcinoma in histopathological examination after treatment with immune checkpoint inhibitors - Asano, Yohei; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Higuchi, Takashi; Taniguchi, Yuta; Morinaga, Sei; Horimoto, Takashi; Nakai, Masaharu; Kadono, Yoshifumi; et al. (Frontiers in Immunology, 2022)
Recently, the prognosis of metastatic renal cell carcinoma (mRCC) has improved owing to the development of immunotherapy using immune checkpoint inhibitors (ICIs). However, there have been few studies on the therapeutic effect of ICIs in bone metastases from renal cell carcinoma (RCC). We report a case in which pulmonary and humeral metastases from RCC were significantly ameliorated using ICIs, while surgery for a pathological fracture of the humerus significantly improved the patient’s quality of life (QoL). A 70-year-old man who underwent a left nephrectomy for RCC developed multiple pulmonary metastases and humeral metastasis with a pathological fracture one year after surgery, and combined treatment with nivolumab and ipilimumab was initiated. After four courses of ICI treatment, multiple pulmonary metastases had almost disappeared, and the tumor at the fracture site had shrunk remarkably. However, the shoulder joint function had decreased due to the fracture, worsening his QoL. Therefore, he underwent surgery and returned to normal daily life one month after. Postoperative histopathological examination of bone and soft tissue at the fracture site revealed no malignancy. To our knowledge, this is the first case report of complete remission of bone metastasis of RCC based on histopathological examination with ICI treatment.